Ultrathin atomic Mn-decorated formamide-converted N-doped carbon for efficient oxygen reduction reaction. Issue 34 (15th August 2019) - Xiong, Xuya; Li, Yajie; Jia, Yin; Meng, Yu; Sun, Kai; Zheng, Lirong; Zhang, Guoxin; Li, Yaping; Sun, Xiaoming
Abstract : Maximum catalysts utilization and enhanced electrocatalytic oxygen reduction performance was achieved by ultrathin deposition of atomically dispersed M-NC on conductive CNT via pyrolysis-free method. Abstract : It is of great importance to control the thickness of catalytic components to enable maximum catalyst utilization and strong catalyst–substrate interaction since electrocatalytic reactions occurring at the interface of catalysts involve a one or two-atom thick active layer. Herein, we achieved an ultrathin deposition of a 2.5 ± 0.2 nm active layer containing atomically dispersed Mn–nitrogen–carbon (Mn–NC) materials on conductive carbon nanotubes (CNTs) via a solvothermal treatment of formamide and Mn salt, and applied the as-made Mn–NC/CNT composite without pyrolysis directly as a catalyst for the oxygen reduction reaction (ORR). The atomic dispersion of Mn species in multiple nitrogen surroundings has been confirmed by combining high-angle annular dark-field scanning transmission electron microscopy, X-ray absorption spectroscopy, and X-ray photon spectroscopy. The as-prepared formamide-converted Mn–NC/CNT composite, used for catalyzing the ORR, exhibited a highly comparable performance in alkaline media relative to that of 20 wt% Pt/C by achieving a high onset potential and a half-wave potential ( E 1/2 ) of 0.91 V and 0.83 V ( vs. RHE), respectively. Density functional theory (DFT) calculations further suggested that Mn–N moieties were capable of efficiently accelerating the release of *OH intermediates under a high reduction potential, thus exhibiting advanced ORR performance.